Evaluation of the Toxicological Effects of Zinc Oxide Nanoparticles in Albino Male Mice - Razooki, Sarab Mohammed M.; Rabee, Adel M. (Iraqi Journal of Science, 2020)
The acute and sub chronic toxicity effects of 25.16 nm intraperitoneally- injected zinc oxide nanoparticles (ZnO NPs) were evaluated. Albino male mice were exposed to three different doses (25, 50 ,and 100 mg/kg ), depending on the value of calculated LD50, for 2 and 4 weeks . Considerable changes in organ indexes were shown with a good relevance to the illustrated histopathological effects which ranged from multiple hemorrhagic foci in liver, mild swelling and dilatation in kidney tubules, thickening of intestinal villi, moderate interstitial pneumonia, especially with the high dose , and sever necrosis of seminiferous tubules in testes of all studied groups. Significant changes in both hematological and biochemical parameters as well as thyroid hormones were observed with a considerable increase in the levels of antioxidant enzymes, in dose and exposure time dependent manner. The highest accumulated Zn mean values were recorded in the small intestine, kidney, liver, and spleen, respectively, followed by testes , heart , lung , and brain. These values followed the same order of the dose dependent manner, which explains the adverse effects that were recorded. This study proved the ability of using organ indexes as good tools side by side with the biochemical indicators to explain the histopathological changes. This study also revealed some histopathological effects that were not previously recorded as a toxicological effect of ZnO NPs in animal models.